Adherence of ukrainian student youth to healthy lifestyle behavior - Tsybulin, Alexander; Yakymenko, Igor; Shapovalov, Yevhenii (My University, 2017)
Over 70% of students admitted negative effects of the environment on their health. In conclusion, Ukrainian student youth demonstrate better adherence to healthy lifestyle as compared to older generations, but smoking and alcohol consumption are the significant threats to young people health. And, unfortunately, more than half surveyed students can be classified as food unsecured.
Keywords: здоров'я; health; healthy lifestyle; food; здоровий спосіб життя; їжа; кафедра харчової хімії; кафедра екології та екоменеджменту